Matilda (Schooner : 1784) certification - Matilda (Schooner : 1784)
Certification for the schooner Matilda, sailing from the port of New York, N.Y., to Baltimore, Md., under the command of Simon White.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: White, Simon; Harbors -- Maryland -- Baltimore; Harbors -- New York (State) -- New York; Ship's papers -- 18th century